The Endocannabinoid System Contributes to Electroacupuncture Analgesia - MacDonald, Iona J.; Chen, Yi-Hung (Frontiers in Neuroscience, 2021)
The extensive involvement of the endocannabinoid system (ECS) in vital physiological and cognitive processes of the human body has inspired many investigations into the role of the ECS and drugs and therapies that target this system and its receptors. Activation of cannabinoid receptors 1 and 2 (CB1 and CB2) by cannabinoid treatments, including synthetic cannabinoids, alleviates behavioral responses to inflammatory and neuropathic pain. An increasing body of scientific evidence details how electroacupuncture (EA) treatments achieve effective analgesia and reduce inflammation by modulating cannabinoid signaling, without the adverse effects resulting from synthetic cannabinoid administration. CB1 receptors in the ventrolateral area of the periaqueductal gray are critically important for the mechanisms of the EA antinociceptive effect, while peripheral CB2 receptors are related to the anti-inflammatory effects of EA. This review explores the evidence detailing the endocannabinoid mechanisms involved in EA antinociception.